The Effect of the Penal Ruling on the Appointment of the Policeman and On the Termination of His Service - Mousa, Nooradeen; Hussein, Alaa (Journal of Legal Sciences, 2026)
The first effect of the criminal ruling on the career position of a policeman appears when it is a condition preventing appointment and reappointment to the police service, and this effect continues when it causes the termination of the policeman’s job, either permanently, such as expulsion from service, or temporarily, as in the case of removal from service The problem lies in the fact that some of the effects of the criminal ruling are regulated by a non-criminal law, such as the Internal Security Forces Service and Retirement Law No.(18) of 2011 (amended), and also that some of the legal texts contained within the scope of the Internal Security Forces Criminal Law, whether in the Internal Security Forces Penal Code No.(14) of 2008 (amended) The Code of Criminal Procedure for the Internal Security Forces, Rum (17) of 2008, was drafted in a manner inconsistent with the general rules regarding the impact of the criminal ruling on public employment, contained in the Iraqi Penal Code No.(111) of 1969 (amended).Therefore, we aim to diagnose these texts and propose the necessary amendments to them in a manner consistent with the general rules of the Iraqi Penal Code.